The Male Perspective on the Underrepresentation of Women in Senior Management Positions of Hotels - Emons, Carlijn (Student Undergraduate Research E-journal!, 2019)
Even though women represent the largest number of workers in the global hotel industry, few are found in top managerial positions. The purpose of this paper is to raise awareness on the underrepresentation of women in senior management positions of hotels, by taking a male perspective on the subject. A qualitative research approach was used to explore personal perceptions on organisational culture, work-life balance, gender equality and competences and skills. Twelve interviews with male managers working in the Dutch hotel industry were conducted. The findings provide important implications on the individual, organisational and national level.